A Guzhangian (late Middle Cambrian) fauna from the Gidgealpa 1 drillhole, Warburton Basin, South Australia. Issue 3 (3rd July 2021) - Sun, X. W.; Bentley, C. J.; Jago, J. B.
Abstract: A Cambrian Series 3 (Guzhangian, Boomerangian) fauna is described from Core 12 of the Gidgealpa 1 drillhole from the Warburton Basin, northeastern South Australia. There are four agnostoid taxa: Ammagnostus laiwuensis, Lejopyge calva, L. armata and an unassigned pygidium, and six polymerid trilobite taxa: Fuchouia sp., Dorypyge sp., Solenoparia changi sp. nov., Pianaspis sp., an unassigned cranidium and an unassigned pygidium. This fauna suggests a correlation with the Goniagnostus nathorsti Zone or the lower part of the Lejopyge laevigata Zone (Boomerangian on the northern Australian biostratigraphic scheme), with the latter preferred. These are the first published descriptions of fossils of this age from the Warburton Basin. Xiaowen Sun [Xiaowen_s@yahoo.com.au ], Sun Petroleum Geoservices, 4 Jolie Grove, Box Hill, Victoria 3128, Australia; Christopher J. Bentley [ bigfossil@bigpond.com ], 30 Albert Street, Clare, South Australia, 5453, Australia; James B. Jago [jim.jago@unisa.edu.au ], University of South Australia–STEM, Mawson Lakes, South Australia 5095, Australia.